Temperature- and solvent-induced solid-state emission changes and AIEE property of a pyrene-based sulfide compound. (June 2020) - Sun, Hao; Wei, Jian-Hua; Xu, Li-Hua; Jiang, Yan; Miao, Bao-Xi; Ni, Zhong-Hai
Abstract: A new organic compound PyStBu was designed and synthesized, which exhibits successive solid-state emission changes induced by heating and DCM vapours fuming. Intermolecular interaction changes or heat-induced crystal surface layer changes may be reasonable for the emission change of Cc-form after heating. In addition, crystal packing changes may be the dominant reason for different photophysical properties of Cc-H-form and P-1-form after DCM fuming. These observations provide reference for tuning property of organic solid-state luminescence materials and designing smart crystal luminescent materials. In addition, PyStBu exhibits aggregation-induced emission enhancement (AIEE) property with interesting "on–off–on" optical switching behavior. Graphical abstract: Image 1 Highlights: A new organic compound PyStBu was synthesized in high yields. PyStBu exhibits successional solid-state emission changes induced by heating and DCM vapours fuming. PyStBu exhibits AIEE property with interesting "on–off–on" optical switching behaviour.